Proportion of unplanned pregnancies, their determinants and health outcomes of women delivering at a teaching hospital in Sri Lanka - Iddamalgoda Dissanayakage Jayani Chalindra Ranatunga; Kapila Jayaratne (BMC, 2020)
Abstract Background Unplanned pregnancy is a significant public health issue in both low- and high-income countries. The burden of unplanned pregnancy is reflected in women opting for pregnancy terminations and it can be detrimental to the women and her family as well as the health system and society. Solid data on the proportion of unplanned pregnancies are using more specific tools such as the London Measure of Unplanned Pregnancy (LMUP) needed to address the issue in Sri Lankan contexts. The objective was to describe the proportion of unplanned pregnancies, their determinants and the health outcomes of women delivering at Colombo North Teaching Hospital-Ragama (CNTH). Methods A cross-sectional study was carried out among 494 consecutive pregnant women selected by non-probability consecutive sampling who were admitted for the confinement at CNTH. A pre-tested structured interviewer-administered questionnaire was used to collect data on antenatal women and intentionality measured by self-administered six-item LMUP. Maternal and newborn health outcomes were ascertained in each post-partum women before discharge. Data were analyzed with the Mann-Whitney U tests, Kruskal-Wallis tests and spearman rank correlation. We also evaluated the psychometric properties of the Sinhalese version of LMUP. Results The response rate was 97.8 and 17.2% of pregnancies ending at birth were unplanned, 12.7% were ambivalent and 70.1% were planned. Associated factor profile of women with unplanned pregnancies includes; not married women (p = 0.001), educated up to the passing of GCE ordinary level by women (p <  0.001) and spouse (p <  0.001), primiparity (p = 0.002) and inadequate knowledge on emergency contraceptives (p = 0.037). Less planned pregnancies were also significantly associated with anemia (p = 0.004), low mood for last 2 weeks (p <  0.001), having a partner with problematic alcohol consumption (p <  0.001), presence of Gender-Based Violence (GBV) (p < 0.001), poor relationship satisfaction with partner (p < 0.001) and family (p < 0.001). Inadequate pre-pregnancy preparation and antenatal care were associated with an unplanned pregnancy. No differences were found in neonatal outcomes. Sinhalese version of the LMUP scale was found to be accepted, valid and reliable with the Cronbach's alpha of 0.936. Conclusions A sizeable proportion of pregnancies were unplanned. Teenage pregnancies, non-marital relationships and inadequate knowledge on emergency contraceptives, maternal anemia, low mood, and GBV were modifiable associated factors which could be prevented by evidence-based locally applicable approaches.